Recent advances in the in-plane shear testing of Mg alloy sheets - Mahesh Panchal; Lalit Kaushik; Ravi K．R．; Rajesh Khatirkar; Shi-Hoon Choi; Jaiveer Singh (Journal of Magnesium and Alloys, 2023)
Sheet-metal products are integral parts of engineering industries and academia research. Various testing techniques have revealed the deformation behaviors of sheet metals under complex stress states. Information obtained from tensile and compression tests, however, are insufficient for the identification of material parameters relevant to modern constitutive laws, which require experimental setups capable of generating various loading conditions and applying great amounts of strain to sheet metals. In-plane shear testing has emerged as an important method to overcome the challenges associated with tension and compression tests and can provide additional information about deformation behaviors under large plastic strains. Materials such as Mg alloys with poor levels of both ductility and formability cannot accommodate large plastic strains. Therefore, tension and compression tests have limitations in explaining the material behaviors that occur during sheet metal forming where large plastic strains are introduced. Many studies have been conducted to explain the deformation behaviors of Mg alloys under shear deformation techniques. These include severe plastic deformation (SPD), especially the equal channel angular pressing (ECAP) and equal channel angular extrusion, rolling combined with shear deformation i.e. differential speed rolling (DSR), and also in-plane shear for sheet metals, particularly under large levels of plastic strain. These in-plane shear technique involves the Miyauchi shear test, ASTM shear test, and twin bridge shear tests. Moreover, many experimental results have revealed that the evolution of microstructure and texture during in-plane shear is closely related to the failure behavior of materials. Therefore, this review is focused on techniques for in-plane shear testing that have been reported thus far, on the effect of in-plane shear on the microstructure development of Mg alloy sheets, and on the usefulness of in-plane shear testing to evaluate the formability of Mg alloy sheets.